Modern Arab Art: Formation of Arab Aesthetics by Nada M. Shabout (Gainesville: University Press of Florida, 2007. 240 pages.) (American Journal of Islam and Society, 2009)
This book endeavors to define a specific term for modern Arab art, which ismost often considered a continuation of Islamic or ethnic art or a subordinatecopy of western trends. This academic text, which targets audiences interestedin contemporary art or the Arab world, or both, is divided into threeparts: “Background and Definitions,” “Modern Arab Aesthetics,” and “The Arabic Letter in Art.” It contains forty images within the text and thirty-twoplates of contemporary works of art by Arabs ...